It's What You Make of It: Founder Identity and Enacting Strategic Responses to Adversity - Powell, E. Erin; Baker, Ted (Academy of Management Journal, 2014)
We conducted a longitudinal field study of 13 resource-constrained founder-run textile and apparel firms to understand how and why firms vary in their strategic responses to the same adversity. We discovered that founders enact distinctly different definitions of the adversity and use their firms as vehicles to defend who they are or to become who they want to be. Bridging two formerly disparate social psychological theories of identity, we develop grounded theory and a process model that together contribute toward our understanding of how and why differences in the structure of founder identity—the set of identities that is chronically salient to a founder in her/his day-to-day work—drive patterned differences in firms' strategic responses. The processes we describe help explain responses to adversity and also provide a platform for research that may generate new insights into the significance for founders of bringing “who I am” into closer alignment with “who I want to be.”